The dragon princess - Baker, E. D. (New York : Bloomsbury, 2008)
Although a princess, Millie cannot keep herself from turning unexpectedly into a dragon, so she ventures off to the Frozen North to find the Blue Witch, who she hopes will help her learn to control her dragon magic.
Horn Book, April 2009.
Voice of Youth Advocates (V.O.Y.A.), December 2008.
5.3
3-6
820L
U
Keywords: Princesses -- Fiction; Dragons -- Fiction; Magic -- Fiction; Princesses -- Fiction; Dragons -- Fiction; Magic -- Fiction; Humorous stories; Princesses -- Fiction; Humorous fiction; Fairy tales